Inventory System Design For PT Mechanical Electrical Provider - Muhamad Noer Rahman Aziz; Erlinda Yunus (Business Review and Case Studies, 2023)
PT Mechanical Electrical Provider (an alias name, henceforth MEP) is a company that focuses on the telecommunications sector as a mechanical & electrical supplier. It was found that the company was still experiencing inventory problems, such as needing more goods and excess goods from its inventory system. Therefore, this study aims to analyze the inventory problems and provides recommendations for the inventory system design. This study uses a qualitative approach by interviewing five officers and staffs in the Procurement Division. Next, this study uses fishbone analysis to find the causes of the problems faced by PT MEP. The Fishbone diagram shows several causes of the inventory problems: people, equipment, method, and material causes. This study uses the quantitative approach by applying the ABC Classification to determine the classification of each item and the best way to control it. There are 6 A-class items, 14 B-class items, and 21 C-class items pada PT MEP. From the ABC classification, A-class products use the Continuous Review Model (Q-system) calculation for an optimal amount and the right time of replenishing inventory. For class B and C classification, the design suggests a Periodic Review Model (P-system) to find the optimal amount for refilling using the difference between the target inventory and the amount of inventory at the time of checking. Through the new system, this research expects a more optimal inventory so that the company can reduce the cost losses incurred so far. Keywords: ABC classification, Continuous Review Model (Q-system), Fishbone Diagram, Periodic Review Model (P-system), Telecommunication